A manganese superoxide dismutase (MnSOD) from red lip mullet, Liza haematocheila: Evaluation of molecular structure, immune response, and antioxidant function. Issue 84 (January 2019) - Sirisena, D.M.K.P.; Perera, N.C.N.; Godahewa, G.I.; Kwon, Hyukjae; Yang, Hyerim; Nam, Bo-Hye; Lee, Jehee
Abstract: Manganese superoxide dismutase (MnSOD) is a nuclear-encoded antioxidant metalloenzyme. The main function of this enzyme is to dismutase the toxic superoxide anion (O2 ˉ) into less toxic hydrogen peroxide (H2 O2 ) and oxygen (O2 ). Structural analysis of mullet MnSOD ( MuMnSOD ) was performed using different bioinformatics tools. Pairwise alignment revealed that the protein sequence matched to that derived from Larimichthys crocea with a 95.2% sequence identity. Phylogenetic tree analysis showed that the MuMnSOD was included in the category of teleosts. Multiple sequence alignment showed that a SOD Fe-N domain, SOD Fe-C domain, and Mn/Fe SOD signature were highly conserved among the other examined MnSOD orthologs. Quantitative real-time PCR showed that the highest MuMnSOD mRNA expression level was in blood cells. The highest expression level of MuMnSOD was observed in response to treatment with both Lactococcus garvieae and lipopolysaccharide (LPS) at 6 h post treatment in the head kidney and blood. Potential ROS-scavenging ability of the purified recombinant protein (rMuMnSOD) was examined by the xanthine oxidase assay (XOD assay). The optimum temperature and pH for XOD activity were found to be 25 °C and pH 7, respectively. Relative XOD activity was significantly increased with the dose of rMuMnSOD, revealing its dose dependency. Activity of rMuMnSOD was inhibited by potassium cyanide (KCN) and N-N′-diethyl-dithiocarbamate (DDC). Moreover, expression of MuMnSOD resulted in considerable growth retardation of both gram-positive and gram-negative bacteria. Results of the current study suggest that MuMnSOD acts as an antioxidant enzyme and participates in the immune response in mullet. Highlights: MnSOD was recognized from the constructed red lip mullet cDNA data base. Antioxidant activity of MuMnSOD was investigated by conventional XOD assay. Antibacterial activity of MuMnSOD was determined by antibacterial assay. MuMnSOD transcripts were extremely detected in blood followed by liver. Time course experiment showed the transcriptional modulation of MuMnSOD upon PAMPs.